HUBUNGAN ANTARA TINGKAT KECEMASAN DENGAN MEKANISME KOPING PADA PASIEN GAGAL JANTUNG KONGESTIF DI UNIT RAWAT RS GRIYA KEDOYA JAKARTA BARAT TAHUN 2023 - Ayuningtyas, Mia; sugiyono; Erlangga Haq, Yogie (STIKes IMC Bintaro, 2024)
Background: Heart failure or CHF (Congestive Heart Failure) is a very serious condition because the death rate caused by heart failure every year continues to increase. Objective: To find out the relationship between anxiety levels and coping mechanisms in congestive heart failure patients in the Inpatient Unit of Grha Kedoya Hospital, West Jakarta in 2023. Method: using the method or technique of Quota Sampling. The analysis technique uses the Chi-square test, which is a statistical test used to test the significance of two variables. Results: showed that there was no anxiety/normal-mild as many as 16 (44.4%), moderate-severe anxiety as many as 20 (56.6%) and the results of bivariate analysis also showed that mal-adaptive coping mechanisms were 12 (33.3%) and adaptive coping mechanisms were 24 (66.7%) with p-values of (P=0.018<0.05) with OR values (95% CI) of 7,000 (1,252–39,149). Conclusion: it can be concluded that Ho is rejected and Ha is accepted, this shows that there is a significant relationship between the relationship between anxiety level and coping mechanism. Keywords: Anxiety Level; Coupling mechanism; Congestive Heart Failure Patients